Digital navigation and the driving-machine: supervision, calculation, optimization, and recognition. Issue 4 (4th July 2019) - Hind, Sam
ABSTRACT: In this paper, I explore the navigational implications of a possible driving world. In the last few years, autonomous vehicles (AVs) have garnered significant attention, with much of this scrutiny centered on the technical possibilities, legal restrictions, and utilitarian ethics of AVs. In this paper, I look at how AVs are radically transforming the nature of navigational decision-making. Research into the automation of industrial processes and aircraft fly-by-wire systems suggests that navigational supervision, by humans, will become a significant duty, recalibrating navigation itself. I draw out the implications of automation through three navigational practices of the 'driving-machine' I refer to as route-calculation, terrain-optimization, and object-recognition. Attending to these practices assists in the ongoing interrogation of the machinic rendering of automobile space.